A case of single ventricular heart, pulmonary atresia, patent ductus arteriosus, major aortopulmonary collateral arteries - Nair, Rema V; Nair, Velayudhan; Mookambika, RV; Rao, RG Mohandas; Somayaji, SN (Asian Journal of Medical Sciences, 2015)
We report a case of multiple congenital anomalies in a female newborn infant, born to themother from a hill tribe. The Doppler echocardiography of the baby showed large atrial septaldefect amounting to single atrium, atretic left atrioventricular valve, large single right sidedventricle, aorta shifted to the left arising from single ventricle and diminutive hypoplasticleft ventricle. Right atrioventricular valve was normal forming single inlet into the ventricle.Pulmonary artery was small and hypoplastic and no antegrade fl ow was observed in it. Thepatient was diagnosed as having single ventricle, pulmonary atresia, patent ductus arteriosus(PDA) and major aortopulmonary collateral artery (MAPCA). DOI: http://dx.doi.org/10.3126/ajms.v6i4.7660 Asian Journal of Medical Sciences Vol.6(4) 2015 96-98